Insights into γ-irradiation effect on hole structure and conductivity of doped ethylene–propylene–diene rubber with different wheat husk fibers lengths - Hamdy F. M. Mohamed; Howayda G. Taha; Islam T. Zedan; Esam E. Abdel-Hady; Mohamed H. M. Hassanien; Hossam B. Alaa (Scientific Reports)
Abstract In this paper, three samples of ethylene–propylene–diene monomer rubber (EPDM)/wheat husk fibers (WHF) with short (SW30), medium (EW30), and long (HW30) lengths of WHF were investigated as a function of γ-irradiation dose up to 300 kGy. The swelling coefficient Q of the toluene, benzene, and chloroform solvents was performed, and the Q reflects the ability of the polymer composites to absorb and retain a solvent within their structure. The conductivity of the examined composites has been computed, and their dielectric characteristics have been calculated. It was found that the dielectric constant exhibited frequency-dependent behavior indicating enhanced charge carrier mobility. The conduction mechanisms in the composites were found to be quantum mechanical tunneling and correlated barrier hopping, depending on the composite and irradiation dose. The γ-irradiation dose dependence of the free volume size, deduced from positron annihilation lifetime spectroscopy, is increasing for the SW30 composite while it decreases for both EW30 and HW30 composites. Increasing the free volume hole size is connected to the degradation effect on the SW30 samples. For EW30 and HW30, there is shrinkage of free volume in the composites due to crosslinking induced by γ-irradiation. Additionally, the nanoscopic properties derived from PAL spectroscopy are correlated with the macroscopic properties of the composites.